Beginning Teacher Induction in Chile: Change over Time - Flores-Gomez, C (Elsevier Ltd, 2019)
This article examines induction practices of two beginning teachers from a city in northern Chile. It specifically draws on the theory of practice architectures to explore and understand the arrangements and conditions that enable and constrain the practices of these beginning teachers at work. The study draws on individual and follow-up email interviews conducted over a period of fifteen months. Responses revealed a number of enabling and constraining conditions relating to particular cultural-discursive, material-economic and social-political conditions that influenced the practice of these beginning teachers. Results further show that support provided by the external self-created network was the most important form of induction mentioned. © 2019 Elsevier Ltd